The use of pupillometry in the assessment of cardiac autonomic function in elite different type trained athletes - Kaltsatou, A.; Kouidi, E.; Fotiou, D.; Deligiannis, P. (European Journal of Applied Physiology, 2011)
The aim of the present study was to evaluate cardiac autonomic function by pupillometry in male athletes. Fifteen elite endurance- (END) and eleven power-trained (POWER) athletes and fifteen sedentary individuals (CONTROL) were studied. All subjects underwent three pupillometric measurements: at rest, peak exercise testing and recovery phase. The pupillometric indices studied were: baseline pupil radius (R1), minimum pupil radius (R2), maximum constriction velocity (VCmax), maximum constriction acceleration (ACmax), amplitude (AMP, R1-R2), constriction ratio (AMP%). During exercise, RR intervals were obtained for each subject with a Polar S810i for time and frequency domain heart rate variability (HRV) analysis. The following parameters of HRV were measured: standard deviation of all NN intervals (SDNN), the mean square successive differences (rMSSD), percent of NN intervals differing >50 ms from the preceding NN (pNN50), low (LF)- and high (HF)- frequency components of the autoregressive power spectrum of the NN intervals and their ratio (LF/HF). At rest and recovery, END showed significantly increased VCmax and ACmax compared to POWER and CONTROL. AMP% was significantly greater in END at rest, peak exercise and recovery compared to POWER and CONTROL. END and POWER had significantly greater AMP at rest and recovery compared to CONTROL. Moreover, all HRV indices were significantly increased in END compared to POWER and CONTROL. However, POWER showed significantly increased rMSSD and LF compared to CONTROL. HRV parameters were significantly correlated with pupillometric parameters during exercise. Our results indicated that any kind of exercise training and mainly endurance one affects autonomic regulation of pupillary light reflex.